The 'unimaginable' chaos continues - Abd Razak, Dzulkifli (2006)
HIJACKING. This was what the recent "foiled terrorist plot" did at London's Heathrow airport. The "foiled terrorist plot" hijacked the world's attention on the killing of thousands of innocent people in Lebanon and Palestine and the wanton destruction of their homes. British police sources said attacks were imminent, involving suicide bombers using chemical bombs smuggled on board planes as drinks. The plot was meant to blow up as many as 10 USbound airplanes in midair, resulting in what was termed as "mass murder on an unimaginable scale". What seems strange is that the killings that had gone on for a month in countries like Lebanon and Palestine have never been described as "unimaginable" on any scale.